Protective Role of Platelets in Myocardial Infarction and Ischemia/Reperfusion Injury - Kornela Hałucha; Alina Rak-Pasikowska; Iwona Bil-Lula (Cardiology Research and Practice)
Thrombotic occlusion of the coronary artery is a key component in the pathogenesis of myocardial ischemia and myocardial infarction (MI). The standard therapy for ischemia is revascularization and restoration of blood flow to previously ischemic myocardium. Paradoxically, reperfusion may result in further tissue damage called ischemia/reperfusion injury (IRI). Platelets play a major role in the pathogenesis of MI and IRI, since they contribute to the thrombus and microthrombi formation, inflammation, release of immunomodulatory mediators, and vasoconstrictive molecules. Antiplatelet therapies have proven efficacy in the prevention of thrombosis and play a protective role in cardiac IRI. Beyond the deterioration effect of platelets in MI and IRI, in the 90s the first reports on a protective effect of molecules released from platelets during MI appeared. However, the role of platelets in cardioprotection is still poorly understood. This review describes the involvement of platelets in MI, IRI, and inflammation. It mainly focuses on the protective role of platelets in MI and IRI. Platelets are involved in cardioprotection based on platelet-releasing molecules and antiplatelet therapy, apart from antiaggregatory effects. Additionally, the use of platelet-derived microparticles as possible markers of MI, with and without comorbidities, and their role in cardioprotection are discussed. This review is aimed at illustrating the present knowledge on the role of platelets in MI and IRI, especially in a context of cardioprotection.